Application of micro-nano reclaimed rubber in preparation of solid tire core rubber or solid tire crown rubber
By using micro-nano recycled glue in solid tire crown glue and core glue, the problems of high Mooney viscosity and slow vulcanization speed during the preparation of existing tire recycled glue are solved, and more efficient vulcanization, better performance and lower environmental impact are achieved.
Patent Information
- Application Number
- CN202411839709.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
When preparing solid tire crown glue and core glue, existing tire recycled glue has problems such as high viscosity, slow vulcanization speed, low production efficiency, poor durability and serious environmental pollution.
Micro-nano recycled glue (MOMN-RGTR) was introduced into the formula of crown glue and core glue. By adjusting the formula and process flow, the Mooney viscosity is significantly reduced, the vulcanization efficiency and tear resistance are improved, and energy consumption and environmental pollution are reduced.
The Mooney viscosity reduction, vulcanization efficiency, tear resistance and aging resistance of solid tire crown glue and core glue are achieved, while reducing energy consumption and environmental pollution during the production process.
Smart Images

Figure CN119661911A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tire manufacturing, and in particular to application of micro-nano recycled rubber in preparing solid tire core rubber or solid tire crown rubber. Background Art
[0002] The rubber layer of solid tires includes crown rubber, core rubber and base rubber. The core rubber is located between the crown rubber and the base rubber, and the rubber layer is thicker. It needs to have good fluidity and vulcanization characteristics, hardness (Shore A67±2), resilience (≥30), mechanical properties (tensile strength ≥16MPa, elongation at break ≥400%, 300% tensile stress ≥10MPa), high tearing performance (tear strength ≥60N / m), aging resistance and low compression heat generation performance (heat generation temperature ≤40℃), especially the tearing performance and compression heat generation resistance of the rubber. The crown rubber is located at the outermost layer of the solid tire and contacts the ground. The rubber compound needs to have good fluidity and vulcanization characteristics, hardness (Shore A70±2), resilience (≥30), mechanical properties (tensile strength ≥17MPa, elongation at break ≥450%, 300% tensile stress ≥8MPa), tearing performance (tear strength ≥80N / mm), aging resistance and wear performance (Akron wear volume ≤0.4cm 3 / 1.61Km), especially the tearing and abrasion resistance of the rubber.
[0003] At present, tire recycled rubber (TRR) is widely used in the crown rubber or core rubber of solid tires. The main preparation method of TRR is to adopt high-temperature dynamic desulfurization method. Its preparation process has problems such as disorderly discharge of wastewater and exhaust gas, high energy consumption, low production efficiency, great safety hazards and strong odor of recycled rubber. In addition, the crown rubber and core rubber of solid tires prepared by TRR have relatively high Mooney viscosity and slow vulcanization speed, which limits the production efficiency and durability of solid tires. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides an application of micro-nano recycled rubber in the preparation of solid tire core rubber or solid tire crown rubber. The present invention significantly reduces the Mooney viscosity of the solid tire core rubber and the solid tire crown rubber by introducing micro-nano recycled rubber into the formula of solid tire crown rubber or solid tire core rubber, thereby improving the vulcanization efficiency as well as the tear resistance and aging resistance. At the same time, the present invention also effectively reduces the energy consumption caused by the use of TRR in the preparation process, greatly reduces environmental pollution, and especially significantly reduces the generation of wastewater.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first object of the present invention is to provide an application of micro-nano reclaimed rubber in the preparation of solid tire crown rubber.
[0007] Preferably, the solid tire crown rubber is made of the following raw materials in parts by weight: Malaysian standard rubber-20#, 88 parts to 92 parts; styrene-butadiene rubber SBR1502, 8 parts to 12 parts; carbon black S660, 18 parts to 22 parts; super carbon black N220, 38 parts to 42 parts; filler CS-B, 23 parts to 27 parts; light truck tire rubber powder, 13 parts to 17 parts; ZnO, 4 parts to 6 parts; stearic acid SA, 2.3 parts to 2.7 parts; parts; antioxidant 4010 and antioxidant RD, 2.3 parts to 2.7 parts; dispersant CS-101A, 1.8 parts to 2.2 parts, low heat generation aid B-206, 1.8 parts to 2.2 parts; tear-resistant resin 2066, 1.8 parts to 2.2 parts; sulfur, 1.4 parts to 1.8 parts; accelerator NS, 0.5 parts to 0.9 parts; anti-scorch agent CTP, 0.1 parts to 0.3 parts; micro-nano recycled rubber, 10 parts to 60 parts.
[0008] Preferably, the mass ratio of antioxidant 4010 to antioxidant RD is 3:2.
[0009] Preferably, the solid tire crown rubber is prepared according to the following steps:
[0010] The Malaysian standard rubber-20#, styrene-butadiene rubber SBR1502, super carbon black N220, filler CS-B, rubber powder, stearic acid SA, ZnO, antioxidant, low heat generation additive B-206, tearing resin 2066, anti-scorch agent CTP, and dispersant CS-101A are mixed for the first time in sequence to obtain a crown masterbatch; the crown masterbatch is mixed for the second time to obtain a crown mixed rubber; micro-nano recycled rubber, accelerator NS and sulfur are added to the crown mixed rubber in sequence for vulcanization to obtain a crown vulcanized rubber; the vulcanized rubber is mixed for the third time to obtain a solid tire crown rubber.
[0011] Preferably, when preparing the solid tire crown rubber, the temperatures of the first mixing, the second mixing, the third mixing and the vulcanization are all 100°C to 110°C.
[0012] The second object of the present invention is to provide an application of micro-nano reclaimed rubber in the preparation of solid tire core rubber.
[0013] Preferably, the solid tire core rubber is made of the following raw materials in parts by weight:
[0014] Malaysian standard rubber-20, 78 to 82 parts; butadiene rubber BR9000, 18 to 22 parts; low-structure medium-reinforcement carbon black N550, 28.8 to 31.2 parts; high-wear-resistant carbon black N330, 19.2 to 20.8 parts; white carbon black, 4.5 to 5.5 parts; silicone coupling agent Si-69, 0.4 to 0.6 parts; ZnO, 4.5 to 5.5 parts; hard Fatty acid SA, 2.5 to 3.5 parts; coumarone 1.5 to 2.5 parts; antioxidant RD and antioxidant BLE, 3.0 to 4.0 parts; dispersant, 1.8 to 2.2 parts, low heat generating aid, 1.8 to 2.2 parts; sulfur, 1.4 to 1.8 parts; accelerator NS, accelerator DM, accelerator DTDM, 1.4 to 1.8 parts; micro-nano recycled rubber, 10 to 60 parts.
[0015] Preferably, the mass ratio of antioxidant RD to antioxidant BLE is 1:1.
[0016] Preferably, the mass ratio of low structure medium reinforcement carbon black N550 and high wear resistant carbon black N330 is 3:2.
[0017] Preferably, the solid tire core rubber is prepared according to the following steps:
[0018] The Malaysian standard rubber-20#, styrene-butadiene rubber BR9000, low-structure medium-reinforced carbon black N550, medium-super carbon black N220, white carbon black, silicone coupling agent Si-69, stearic acid SA, ZnO, coumarone, antioxidant RD and antioxidant BLE, low heat generation aid and dispersant are mixed for the first time in sequence to obtain a tire core masterbatch; the tire core masterbatch is mixed for the second time to obtain a tire core mixed rubber; micro-nano recycled rubber, accelerator NS, accelerator DM, accelerator DTDM and sulfur are added to the tire core mixed rubber in sequence for vulcanization to obtain a tire core vulcanized rubber; the tire core vulcanized rubber is mixed for the third time to obtain a solid tire crown rubber.
[0019] Preferably, when preparing the solid tire core rubber, the temperatures of the first mixing, the second mixing, the third mixing and the vulcanization are all 100°C to 110°C.
[0020] Preferably, the Mooney viscosity of the micro-nano regenerated rubber is 40.8-42.5, the sol content is 41.7%-45%, the gel content is 19%-22.3%, and the particle size is 235nm-243nm.
[0021] Preferably, the micro-nano regenerated rubber is prepared according to the following steps:
[0022] The truck tire rubber powder is placed in a tank-type thermal oxidation degradation equipment, and pulse air with a flow rate of 9mL / min to 21mL / min is introduced. The equipment is thermally oxidized and degraded at 190℃ to 202℃ for 10 minutes to obtain micro-nano regenerated rubber. Under this air flow rate, the micro-nano regenerated rubber produced by the cracking of the truck tire rubber powder can meet the performance index requirements of solid tire crown rubber and solid tire core rubber for micro-nano regenerated rubber.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. Compared with the solid tire core rubber made by using TRR, the solid tire core rubber provided by the present invention has lower Mooney viscosity, higher vulcanization efficiency, and excellent tear resistance and compression heat resistance. When the filling amount of micro-nano recycled rubber is 10 to 50 parts, the solid tire core rubber of the present invention can maintain excellent resilience and mechanical properties, such as tensile strength, elongation at break, tensile stress and permanent deformation at break, which all meet the use requirements of solid tires; compared with the solid tire crown rubber made by using TRR, the solid tire crown rubber provided by the present invention has lower Mooney viscosity, higher vulcanization efficiency, and good wear resistance and tear resistance. When the filling amount of micro-nano recycled rubber is 10 to 60 parts, the hardness, density and resilience of the solid tire crown rubber can meet the use requirements of the solid tire crown rubber.
[0025] In addition, with the increase of micro-nano recycled rubber filling amount, the aging resistance of solid tire core rubber and solid tire crown rubber is significantly enhanced. This is due to the regeneration mechanism of micro-nano recycled rubber, that is, by regulating the oxygen supply rate, the SS bond, CS bond and part of CC bond in the truck tire rubber powder are effectively broken, so that the generated micro-nano recycled rubber has the characteristics of low gel content, high sol content, small molecular weight and wide distribution, which promotes the significant improvement of the fluidity of solid tire core rubber and solid tire crown rubber, and effectively inhibits the re-crosslinking of free radicals during the aging process, thereby enhancing the aging resistance of solid tire core rubber and solid tire crown rubber.
[0026] 2. The application of micro-nano recycled rubber not only effectively improves the processing performance of solid tire core rubber and solid tire crown rubber, but also reduces production costs; in addition, while increasing the recycling rate of truck tire rubber powder, it also reduces pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 These are electron microscope images of carbon black in micro-nano regenerated rubber, where (a) is the SEM image and (b) is the TEM image.
[0028] Figure 2 This is the particle size distribution diagram of carbon black in micro-nano regenerated rubber.
[0029] Figure 3It is a thermal oxidation reactor for micro-nano regenerated rubber, wherein (a) is a diagram of the equipment and (b) is a schematic diagram of the equipment structure.
[0030] Figure 4 The diagram is a rendering of the tearing performance of the core rubber of the solid tires prepared in Comparative Examples 1 to 6 and Examples 1 to 5.
[0031] Figure 5 This is a diagram showing the effect of the compression heating temperature of the solid tire core rubber prepared in Comparative Examples 1 to 6 and Examples 1 to 5.
[0032] Figure 6 These are SEM images of the tire core rubbers prepared in Comparative Examples 1 to Comparative Examples 6 and Examples 1 to Examples 5, wherein (a) is TRR-tire core rubber, (b) is MOMN-RGTR-10-tire core rubber, (c) is MOMN-RGTR-20-tire core rubber, (d) is MOMN-RGTR-30-tire core rubber, (e) is MOMN-RGTR-40-tire core rubber, (f) is MOMN-RGTR-50-tire core rubber, (g) is MOMN-RGTR-60-tire core rubber, (h) is MOMN-RGTR-70-tire core rubber, (i) is MOMN-RGTR-80-tire core rubber, (j) is MOMN-RGTR-90-tire core rubber, and (k) is MOMN-RGTR-100-tire core rubber.
[0033] Figure 7 It is a rendering of the tearing performance of the crown rubber of the solid tires prepared in Comparative Examples 7 to 11 and Examples 6 to 11.
[0034] Figure 8 It is a rendering of the wear performance of the crown rubber of the solid tires prepared in Comparative Examples 7 to 11 and Examples 6 to 11.
[0035] Fig. 9 These are SEM images of the tire crown rubbers prepared in Comparative Examples 7 to 11 and Examples 6 to 11, wherein (a) is TRR-tire crown rubber, (b) is MOMN-RGTR-10-tire crown rubber, (c) is MOMN-RGTR-20-tire crown rubber, (d) is MOMN-RGTR-30-tire crown rubber, (e) is MOMN-RGTR-40-tire crown rubber, (f) is MOMN-RGTR-50-tire crown rubber, (g) is MOMN-RGTR-60-tire crown rubber, (h) is MOMN-RGTR-70-tire crown rubber, (i) is MOMN-RGTR-80-tire crown rubber, (j) is MOMN-RGTR-90-tire crown rubber, and (k) is MOMN-RGTR-100-tire crown rubber. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Among them, light truck tire rubber powder, passed through a 60-mesh sieve; truck tire rubber powder, passed through a 24-mesh sieve; truck tire rubber powder, GTR, which contains: filler oil mass fraction 5.0%, natural rubber mass fraction 40.8%, synthetic rubber mass fraction 13.6%, carbon black mass fraction 31.9%, ash mass fraction 8.7%, purchased from Jiangsu Zhonghong Environmental Protection Technology Co., Ltd.; Malaysian standard rubber -20#, denoted as SMR-20#, its PRI value is 40% to 60%, ash content ≤0.8%, nitrogen content ≤0.60%, volatile matter ≤0.8%, mechanical impurities (44μm sieve) ≤0.15%; the micro-nano recycled rubber is named MOMN-RGTR.
[0038] At present, tire recycled rubber (TRR) is widely used in the crown rubber or core rubber of solid tires. The main preparation method of TRR is to adopt high-temperature dynamic desulfurization method. Its preparation process has problems such as disorderly discharge of wastewater and exhaust gas, high energy consumption, low production efficiency, great safety hazards and strong odor of recycled rubber. In addition, the crown rubber and core rubber of solid tires prepared by TRR have relatively high Mooney viscosity and slow vulcanization speed, which limits the production efficiency and durability of solid tires.
[0039] In view of these technical defects, the present invention provides an application of micro-nano recycled rubber in the preparation of solid tire crown rubber or solid tire core rubber. Compared with solid tire crown rubber and solid tire core rubber prepared by TRR technology, the present invention significantly reduces the Mooney viscosity of solid tire core rubber and solid tire crown rubber by introducing micro-nano recycled rubber into the formula of solid tire crown rubber or solid tire core rubber, thereby improving the vulcanization efficiency and tear resistance and aging resistance. At the same time, the present invention also effectively reduces the energy consumption caused by the use of TRR in the preparation process, greatly reduces environmental pollution, and especially significantly reduces the generation of wastewater.
[0040] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments:
[0041] Example 1
[0042] An application of MOMN-RGTR in preparing a solid tire core rubber comprises the following steps:
[0043] S1. According to the mass parts, weigh 80 parts of SMR-20#, 20 parts of butadiene rubber BR9000, 30 parts of low structure medium reinforcing carbon black N550, 20 parts of high wear-resistant carbon black N330, 5 parts of white carbon black, 0.5 parts of silicone coupling agent Si-69, 5 parts of ZnO, 3 parts of stearic acid SA; 2 parts of coumarone, 3.5 parts of antioxidant RD and antioxidant BLE, 2 parts of dispersant, 2 parts of low heat generating aid, 1.6 parts of sulfur, 1.6 parts of accelerator NS, 1.6 parts of accelerator DM, 1.6 parts of accelerator DTDM, and 10 of MOMN-RGTR.
[0044] S2. Add weighed SMR-20# and BR9000 into an internal mixer preheated to 100°C and mix for 3 minutes; then, add low-structure medium-reinforcement carbon black N550 and high-wear-resistant carbon black N330 and continue mixing for 3 minutes; then add white carbon black and silicone coupling agent Si-69 and mix for another 3 minutes; then add stearic acid SA, ZnO, coumarone, antioxidant RD and antioxidant BLE, low heat generation aid, and dispersant mixture, and continue mixing for 3 minutes until the mixing is completed to obtain a core masterbatch, recorded as MOMN-RGTR / SMR / BR-1.
[0045] S3. Move MOMN-RGTR / SMR / BR-1 to an open mixer for refining and thin pass treatment at 100°C. During the refining stage, adjust the roller distance to 3mm, refining 4 times on each side, and make 4 triangular packages; then thin pass treatment, adjust the roller distance to 0.6mm, and thin pass treatment 6 times on the rubber material; finally, unroll and store, unroll the rubber material with a roller distance of 3mm, and store for 48 hours to obtain the tire core compound rubber, which is recorded as MOMN-RGTR / SMR / BR-2.
[0046] S4. Put the parked MOMN-RGTR / SMR / BR-2 into the internal mixer again, add MOMN-RGTR, and mix at 100°C for 2 minutes; then, add accelerator NS, accelerator DM, accelerator DTDM and sulfur in sequence, and continue mixing for 2 minutes; after mixing, discharge the rubber material to obtain the tire core vulcanized rubber, which is recorded as MOMN-RGTR / SMR / BR-3.
[0047] S5. Move MOMN-RGTR / SMR / BR-3 to an open mixing mill, perform tumbling and thin-pass treatment according to the process of S3, and obtain a solid tire core rubber, namely MOMN-RGTR-core rubber, recorded as MOMN-RGTR-10-core rubber.
[0048] Example 2
[0049] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as the preparation method of Example 1, except that 10 parts of MOMN-RGTR are replaced by 20 parts to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber, recorded as MOMN-RGTR-20-core rubber.
[0050] Example 3
[0051] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as the preparation method of Example 1, except that 10 parts of MOMN-RGTR are replaced by 30 parts to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber, recorded as MOMN-RGTR-30-core rubber.
[0052] Example 4
[0053] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as the preparation method of Example 1, except that 10 parts of MOMN-RGTR are replaced by 40 parts to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber, recorded as MOMN-RGTR-40-core rubber.
[0054] Example 5
[0055] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as the preparation method of Example 1, except that 10 parts of MOMN-RGTR are replaced by 50 parts to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber, recorded as MOMN-RGTR-50-core rubber.
[0056] Example 6
[0057] An application of MOMN-RGTR in preparing a solid tire crown rubber comprises the following steps:
[0058] S1. According to mass parts, weigh 90 parts of SMR-20#, 10 parts of styrene-butadiene rubber SBR1502, 20 parts of carbon black S660, 40 parts of super carbon black N220, 25 parts of filler CS-B, 15 parts of light truck tire rubber powder; 5 parts of ZnO, 2.5 parts of stearic acid SA, 2.5 parts of antioxidant 4010 and antioxidant RD, 2.0 parts of dispersant CS-101A, 2.0 parts of low heat generation aid B-206, 2.0 parts of tear-resistant resin 2066, 1.6 parts of sulfur, 0.7 parts of accelerator NS, 0.2 parts of anti-scorch agent CTP, and 10 parts of MOMN-RGTR.
[0059] S2. Add the weighed SMR-20# and SBR1502 into an internal mixer preheated to 100°C and mix for 3 minutes; then, add the super carbon black N220, filler CS-B and rubber powder, and continue mixing for 3 minutes; then add a mixture of stearic acid SA, ZnO, antioxidant 4010 and antioxidant RD, low heat generation aid B-206, tear resistance resin 2066, anti-scorch agent CTP, and dispersant CS-101A, and continue mixing for 3 minutes until the mixing is completed to obtain a tire crown masterbatch, recorded as MOMN-RGTR / SMR / SBR-1.
[0060] S3. Move MOMN-RGTR / SMR / SBR-1 to the open mill for refining and thin pass treatment. In the refining stage, adjust the roller distance to 3mm, refining 4 times on each side, and make 4 triangular packages; then thin pass treatment, adjust the roller distance to 0.6mm, and thin pass treatment 6 times on the rubber material; finally, unroll and store, unroll the rubber material with a roller distance of 3mm, and store it for 48 hours to obtain the crown compound rubber, which is recorded as MOMN-RGTR / SMR / SBR-2.
[0061] S4. Put the parked MOMN-RGTR / SMR / SBR-2 into the internal mixer again, add MOMN-RGTR, and mix at 100°C for 2 minutes; then, add accelerator NS and sulfur in sequence, and continue mixing for 2 minutes; after the mixing is completed, discharge the rubber material to obtain the crown vulcanized rubber, which is recorded as MOMN-RGTR / SMR / SBR-3.
[0062] S5. Move MOMN-RGTR / SMR / SBR-3 to an open mixing mill, perform treading and thin pass treatment according to the process of S3, and obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-10-crown rubber.
[0063] Example 7
[0064] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that 10 parts of MOMN-RGTR are replaced by 20 parts to obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-20-crown rubber.
[0065] Example 8
[0066] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that 10 parts of MOMN-RGTR are replaced by 30 parts to obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-30-crown rubber.
[0067] Example 9
[0068] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that 10 parts of MOMN-RGTR are replaced by 40 parts to obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-40-crown rubber.
[0069] Example 10
[0070] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that 10 parts of MOMN-RGTR are replaced by 50 parts to obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-50-crown rubber.
[0071] Embodiment 11
[0072] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that 10 parts of MOMN-RGTR are replaced by 60 parts to obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-60-crown rubber.
[0073] Example 12
[0074] An application of MOMN-RGTR in preparing a solid tire core rubber comprises the following steps:
[0075] S1. According to mass parts, weigh SMR-20#, 78 parts, butadiene rubber BR9000, 18 parts, N550 and N330, 48 parts, white carbon black, 4.5 parts, silicone coupling agent Si-69, 0.4 parts, ZnO, 4.5 parts, stearic acid SA, 2.5 parts, coumarone, 1.5 parts, antioxidant RD and antioxidant BLE, 3 parts, dispersant, 1.8 parts, low heat generation aid, 1.8 parts, sulfur, 1.4 parts, accelerator NS, accelerator DM, accelerator DTDM, 1.4 parts, MOMN-RGTR, 50.
[0076] S2. Add weighed SMR-20# and butadiene rubber BR9000 into an internal mixer preheated to 110°C and mix for 4 minutes; then, add N550 and N330 and continue mixing for 4 minutes; then add white carbon black and Si-69 and mix for another 4 minutes; then add stearic acid SA, ZnO, coumarone, RD and BLE, low heat generating additive, and dispersant mixture and continue mixing for 4 minutes until the mixing is completed to obtain a core masterbatch, recorded as MOMN-RGTR / SMR / BR-1.
[0077] S3. Move MOMN-RGTR / SMR / BR-1 to an open mixer for refining and thin pass treatment at 110°C. During the refining stage, adjust the roller distance to 4mm, refining 5 times on each side, and make 4 triangular packages; then thin pass treatment, adjust the roller distance to 0.7mm, and thin pass treatment 8 times on the rubber material; finally, unroll and store, unroll the rubber material with a roller distance of 4mm, and store it for 96 hours to obtain the tire core compound rubber, which is recorded as MOMN-RGTR / SMR / BR-2.
[0078] S4. Put the parked MOMN-RGTR / SMR / BR-2 into the internal mixer again, add MOMN-RGTR, and mix at 110°C for 3 minutes; then, add accelerator NS, accelerator DM, accelerator DTDM and sulfur in sequence, and continue mixing for 3 minutes; after the mixing is completed, discharge the rubber material to obtain vulcanized rubber, which is recorded as MOMN-RGTR / SMR / BR-3.
[0079] S5. Move MOMN-RGTR / SMR / BR-3 to an open mixing mill, perform tumbling and thin pass treatment according to the process of S3, and obtain a solid tire core rubber, namely, MOMN-RGTR-core rubber.
[0080] Embodiment 13
[0081] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as Example 12, except that the mass parts of the raw materials in S1 are replaced by SMR-20#, 82 parts, butadiene rubber BR9000, 22 parts, N550, 31.2 parts, N330, 20.8 parts, white carbon black, 5.5 parts, silicone coupling agent Si-69, 0.6 parts, ZnO, 5.5 parts, stearic acid SA, 3.5 parts; coumarone, 2.5 parts, antioxidant RD and antioxidant BLE, 4 parts, dispersant, 2.2 parts, low heat generating aid, 2.2 parts, sulfur, 1.8 parts, accelerator NS, accelerator DM, accelerator DTDM, 1.8 parts, MOMN-RGTR, 50, to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber.
[0082] Embodiment 14
[0083] An application of MOMN-RGTR in preparing a solid tire crown rubber comprises the following steps:
[0084] S1. According to mass parts, weigh 88 parts of SMR-20#, 8 parts of styrene-butadiene rubber SBR1502, 18 parts of carbon black S660, 38 parts of N220, 23 parts of filler CS-B, 13 parts of light truck tire rubber powder, 4 parts of ZnO, 2.3 parts of stearic acid SA, 2.3 parts of antioxidant 4010 and antioxidant RD, 1.8 parts of dispersant CS-101A, 1.8 parts of low heat generation aid B-206, 1.8 parts of tear-resistant resin 2066, 1.6 parts of sulfur, 0.5 parts of accelerator NS, 0.1 parts of anti-scorch agent CTP, and 60 parts of MOMN-RGTR.
[0085] S2. Add the weighed SMR-20# and styrene-butadiene rubber SBR1502 into an internal mixer preheated to 110°C and mix for 4 minutes; then, add the super carbon black N220, filler CS-B and rubber powder, and continue mixing for 4 minutes; then add a mixture of stearic acid SA, ZnO, antioxidant 4010 and antioxidant RD, low heat generation aid B-206, tear-resistant resin 2066, anti-scorch agent CTP and dispersant CS-101A, and continue mixing for 4 minutes until the mixing is completed to obtain a tire crown masterbatch, which is recorded as MOMN-RGTR / SMR / SBR-1.
[0086] S3. Move MOMN-RGTR / SMR / SBR-1 to an open mixer for refining and thin pass treatment at 110°C. During the refining stage, adjust the roller distance to 3mm, refining 4 times on each side, and make 6 triangular packages; then thin pass treatment, adjust the roller distance to 0.7mm, and thin pass treatment 8 times on the rubber material; finally, unroll and store, unroll the rubber material with a roller distance of 4mm, and store for 96 hours to obtain the crown compound rubber, which is recorded as MOMN-RGTR / SMR / SBR-2.
[0087] S4. Put the parked MOMN-RGTR / SMR / SBR-2 into the internal mixer again, add MOMN-RGTR, and mix at 110°C for 3 minutes; then, add accelerator NS and sulfur in sequence, and continue mixing for 3 minutes; after the mixing is completed, discharge the rubber material to obtain the crown vulcanized rubber, which is recorded as MOMN-RGTR / SMR / SBR-3.
[0088] S5. Move the MOMN-RGTR / SMR / SBR-3 to an open mixing mill, perform treading and thin-pass treatment according to the process of S3, and obtain a solid tire crown rubber, namely, MOMN-RGTR-crown rubber.
[0089] Embodiment 15
[0090] A use of MOMN-RGTR in preparing a solid tire crown rubber has the same preparation steps as Example 14, except that the mass parts of the raw materials in S1 are replaced by 90 parts of SMR-20#, 10 parts of styrene-butadiene rubber SBR1502, 20 parts of carbon black S660, 40 parts of medium super carbon black N220, 25 parts of filler CS-B, 15 parts of light truck tire rubber powder; 5 parts of ZnO, 2.5 parts of stearic acid SA, 2.5 parts of antioxidant 4010 and antioxidant RD, 2.0 parts of dispersant CS-101A, 2.0 parts of low heat generation aid B-206, 2.0 parts of tear-resistant resin 2066, 1.6 parts of sulfur, 0.7 parts of accelerator NS, 0.2 parts of anti-scorch agent CTP, and 60 parts of MOMN-RGTR to obtain a solid tire crown rubber, i.e., MOMN-RGTR-crown rubber.
[0091] Comparative Example 1
[0092] A solid tire core rubber is prepared in the same manner as in Example 1, except that MOMN-RGTR is replaced by TRR to obtain a solid tire core rubber, namely, TRR-core rubber.
[0093] Comparative Example 2
[0094] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as the preparation method of Example 1, except that 10 parts of MOMN-RGTR are replaced by 60 parts to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber, recorded as MOMN-RGTR-60-core rubber.
[0095] Comparative Example 3
[0096] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as the preparation method of Example 1, except that 10 parts of MOMN-RGTR are replaced by 70 parts to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber, recorded as MOMN-RGTR-70-core rubber.
[0097] Comparative Example 4
[0098] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as the preparation method of Example 1, except that 10 parts of MOMN-RGTR are replaced by 80 parts to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber, recorded as MOMN-RGTR-80-core rubber.
[0099] Comparative Example 5
[0100] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as the preparation method of Example 1, except that 10 parts of MOMN-RGTR are replaced by 90 parts to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber, recorded as MOMN-RGTR-90-core rubber.
[0101] Comparative Example 6
[0102] An application of MOMN-RGTR in preparing a solid tire core rubber is the same as the preparation method of Example 1, except that 10 parts of MOMN-RGTR are replaced by 100 parts to obtain a solid tire core rubber, i.e., MOMN-RGTR-core rubber, recorded as MOMN-RGTR-100-core rubber.
[0103] Comparative Example 7
[0104] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that MOMN-RGTR is replaced by TRR to obtain a solid tire crown rubber, namely, TRR-crown rubber.
[0105] Comparative Example 8
[0106] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that 10 parts of MOMN-RGTR are replaced by 70 parts to obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-70-crown rubber.
[0107] Comparative Example 9
[0108] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that 10 parts of MOMN-RGTR are replaced by 80 parts to obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-80-crown rubber.
[0109] Comparative Example 10
[0110] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that 10 parts of MOMN-RGTR are replaced by 90 parts to obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-90-crown rubber.
[0111] Comparative Example 11
[0112] An application of MOMN-RGTR in preparing a solid tire crown rubber is the same as the preparation method of Example 6, except that 10 parts of MOMN-RGTR are replaced by 100 parts to obtain a solid tire crown rubber, namely MOMN-RGTR-crown rubber, recorded as MOMN-RGTR-100-crown rubber.
[0113] The MOMN-RGTR used in the present invention is prepared according to the following steps: 40 kg of GTR is placed in a 200 L self-designed tank-type thermal oxidation degradation device, pulsed air is introduced at 20 mL / min, and thermal oxidation degradation reaction is carried out at 200 ° C for 10 min to obtain micro-nano regenerated rubber, namely MOMN-RGTR. Figure 3 As shown; the test results of MOMN-RGTR chemical indicators are shown in Table 1.
[0114] Table 1 Chemical index table of MOMN-RGTR
[0115]
[0116]
[0117] As shown in Table 1, the Mooney viscosity of the MOMN-RGTR used in the present invention is between 40.8 and 42.5, the sol content is between 41.7% and 45%, the sol molecular weight is between 8866 g / mol and 10000 g / mol, and its elongation at break reaches an excellent performance of 200% to 220%. After comparing with the national standard "Recycled Rubber" (GB / T 13460-2016), the EU RoHS directive, and the requirements for the content of substances of high concern, it can be clearly judged that MOMN-RGTR fully meets environmental protection requirements.
[0118] observe Figure 1 It is known that the unique nanostructure of carbon black in micro-nano regenerated rubber can form a strong bonding adhesive with the raw rubber matrix through physical and chemical reactions. This bonding adhesive is one of the main materials for reinforcing the raw rubber matrix. When the truck tire rubber powder is treated with micro-oxygen degradation, the carbon black in the obtained MOMN-RGTR can dissociate, and a part of the micro-nano regenerated rubber becomes a sol, while the remaining part mainly exists in the form of a gel with carbon black as the main component.
[0119] observe Figure 2 It was found that the particle size of CB was about 239 nm.
[0120] Solid tire core rubbers were prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 6. Mooney viscosity of the solid tire core rubbers prepared in Examples 1 to 5 and Comparative Examples 1 to 6 was measured, and the test results are shown in Table 2.
[0121] Table 2 Mooney viscosity of solid tire core rubber obtained from Example 1 to Example 5 and Comparative Example 1 to Comparative Example 6
[0122]
[0123] It can be seen from Table 2 that the Mooney viscosity of the solid tire core rubber with MOMN-RGTR added is lower than that with TRR added. The main reason is that the regeneration mechanisms of MOMN-RGTR and TRR are different. TRR mainly destroys SS bonds and CS bonds through heat, oxygen (natural mixing, small amount), mechanical force and chemical regeneration agents, while the main chain structure combined with CC bonds is difficult to destroy. The gel content produced is high, reaching more than 70%, and the sol content is low. MOMN-RGTR uses precise oxygen supply to break the cross-linked bonds of truck tire rubber powder, which not only contain SS bonds and CS bonds, but also some CC bonds. The regeneration degree of micro-nano regenerated rubber is large, the generated gel content is small, and the sol content is high. Under the same plastic mixing conditions, the micro-nano regenerated rubber has a small molecular weight and a wide distribution, which effectively promotes the fluidity of the solid tire core rubber, which is manifested as a low Mooney viscosity.
[0124] The vulcanization characteristics of the solid tire core rubbers prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were measured respectively. The test results are shown in Table 3.
[0125] Table 3 Vulcanization characteristics of solid tire core rubber obtained from Examples 1 to 5 and Comparative Examples 1 to 6
[0126]
[0127]
[0128] It can be concluded from Table 3 that as the number of MOMN-RGTR fillings in the solid tire core rubber increases, the MH-ML value shows a gradual downward trend, but when the filling amount is 10 to 40 parts, the degree of influence is relatively small. This shows that when the MOMN-RGTR content is low, it has little effect on the degree of cross-linking of the solid tire core rubber. However, as the number of MOMN-RGTR fillings increases, the gel content also increases, which consumes sulfur and accelerators, which is manifested as a significant decrease in MH-ML; the Mooney scorch time t of the solid tire core rubber filled with MOMN-RGTR 10 Compared with the TRR compound 10The short time indicates that the solid tire core rubber filled with MOMN-RGTR enters the hot vulcanization period earlier, but the change value is small, not only will there be no scorching phenomenon, but also will improve the vulcanization efficiency. This is because the solid tire core rubber filled with MOMN-RGTR has a low Mooney viscosity and good fluidity, which enables the solid tire core rubber to quickly fill the mold and complete vulcanization; in addition, the process vulcanization time t of the solid tire core rubber filled with MOMN-RGTR is 90 and theoretical vulcanization time t 100 Both are lower than the solid tire core rubber filled with TRR, with the maximum reduction reaching 25% and 49%, indicating that MOMN-RGTR can significantly improve the vulcanization efficiency. Due to the small particle size and large specific surface area of MOMN-RGTR, its dispersion in the solid tire core rubber is better than that of TRR, which more effectively promotes the occurrence of cross-linking reaction; with the increase of MOMN-RGTR filling ratio, t 90 and t 100 Both showed a trend of first decreasing and then increasing. When the addition reached 60 parts, the vulcanization time was the shortest. The reason for this phenomenon is similar to the change trend of the MH-ML value, that is, when the MOMN-RGTR filling ratio is large, the gel content in the solid tire core rubber increases, resulting in an increase in the consumption of sulfur and accelerators, which in turn reduces the vulcanization cross-linking speed and prolongs the time to reach the flat period of the solid tire core rubber.
[0129] The resilience of the solid tire core rubbers prepared in Examples 1 to 5 and Comparative Examples 1 to 6 was measured respectively. The test results are shown in Table 4.
[0130] Table 4 Impact elasticity of solid tire core rubber obtained from Examples 1 to 5 and Comparative Examples 1 to 6
[0131]
[0132] It can be concluded from Table 4 that the resilience of the solid tire core rubber filled with MOMN-RGTR is lower than that of the solid tire core rubber filled with TRR, and with the increase of the filling amount of MOMN-RGTR, the resilience of the solid tire core rubber decreases. The main reason is consistent with the reason for the vulcanization characteristics analysis, which is because the degree of cross-linking of the solid tire core rubber is reduced. However, when the filling amount of MOMN-RGTR is 10 to 50 parts, the effect on the resilience is small, and the resilience can still reach more than 30, which does not affect the use of the solid tire core rubber.
[0133] The hardness, tensile properties and aging properties of the solid tire core rubbers prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were tested respectively. The test results are shown in Table 5.
[0134] Table 5 Tensile properties and thermal oxidation aging properties of solid tire core rubber obtained from Examples 1 to 5 and Comparative Examples 1 to 6
[0135]
[0136] It can be concluded from Table 5 that when the filling amount of MOMN-RGTR is greater than 50 parts, the hardness of the solid tire core rubber decreases, which is lower than Shao A65 and can no longer meet the use requirements. This phenomenon of reduced hardness is attributed to the reduction of the crosslinking density of the solid tire core rubber. In addition, with the increase of the filling amount of MOMN-RGTR, the tensile strength of the solid tire core rubber also shows a downward trend. However, when the filling amount of MOMN-RGTR is less than 40 parts, the tensile strength can still be maintained above 16MPa, the elongation at break exceeds 400%, the 300% tensile stress is greater than 10MPa, and the permanent deformation at break is less than 25%. These indicators all meet the performance requirements of the solid tire core rubber. Compared with TRR filled with the same number of parts, the solid tire core rubber filled with MOMN-RGTR is slightly insufficient in mechanical properties. This is mainly because the solid tire core rubber filled with MOMN-RGTR has a low sol content and a high gel content, which leads to a reduced degree of crosslinking involved in the reaction. However, after an aging test at 170℃×72h, the MOMN-RGTR solid tire core rubber filled with the same number of parts showed better aging resistance than the TRR solid tire core rubber. This result shows that the solid tire core rubber filled with MOMN-RGTR has relatively better aging resistance. The reason is that TRR uses a regeneration activator during the desulfurization process. These residual regeneration activators will cause the free radicals generated during the desulfurization process to become the receptors of aging free radicals, thereby preventing the re-crosslinking between the aging free radicals, and then accelerating the occurrence of thermal oxidation aging.
[0137] The Mooney viscosity of the solid tire crown rubbers prepared in Examples 6 to 11 and Comparative Examples 7 to 11 was measured respectively. The test results are shown in Table 6.
[0138] Table 6 Mooney viscosity of solid tire crown rubber obtained from Example 6 to Example 11 and Comparative Example 7 to Comparative Example 11
[0139]
[0140] It can be concluded from Table 6 that compared with the solid tire crown rubber with TRR, the Mooney viscosity of the solid tire crown rubber with MOMN-RGTR is generally lower, and does not reach the maximum Mooney viscosity that TRR can achieve. Specifically, only in the solid tire crown rubber formula with 10 and 20 parts of MOMN-RGTR added, the average Mooney viscosity slightly exceeds the average Mooney viscosity of TRR. When the amount of MOMN-RGTR added exceeds 20 parts, the average Mooney viscosity of the solid tire crown rubber with MOMN-RGTR added is lower than the average Mooney viscosity of TRR.
[0141] The vulcanization characteristics of the solid tire crown rubbers prepared in Examples 6 to 11 and Comparative Examples 7 to 11 were tested respectively. The test results are shown in Table 7.
[0142] Table 7 Vulcanization characteristics of solid tire crown rubber obtained from Examples 6 to 11 and Comparative Examples 7 to 11
[0143] sample <![CDATA[M L (dN.m)]]> <![CDATA[M H (dN.m)]]> <![CDATA[M H -M L (dN.m)]]> <![CDATA[t 10 (s)]]> <![CDATA[t 90 (s)]]> <![CDATA[t 100 (s)]]> Example 6 2.04 10.77 8.73 80 394 682 Example 7 2.00 10.65 8.65 76 392 688 Example 8 1.94 9.94 8.00 69 387 670 Example 9 2.13 9.06 6.93 46 364 654 Example 10 1.94 8.74 6.80 59 361 636 Embodiment 11 2.01 8.47 6.46 56 354 603 Comparative Example 7 2.09 11.23 9.14 82 395 713 Comparative Example 8 2.05 7.89 5.84 53 359 604 Comparative Example 9 1.85 6.81 4.96 44 375 624 Comparative Example 10 1.75 6.14 4.39 32 377 613 Comparative Example 11 1.80 6.11 4.31 41 384 604
[0144] It can be concluded from Table 7 that as the filling amount of MOMN-RGTR increases, the MH-ML value tends to decrease gradually, but when the filling amount is in the range of 10 to 30 parts, the degree of influence is relatively small, indicating that when the content of MOMN-RGTR is low, the degree of cross-linking of the solid tire crown rubber is less affected. However, as the filling amount of MOMN-RGTR increases further, the gel content also increases, which consumes more sulfur and accelerators, resulting in a greater decrease in MH-ML; compared with the solid tire crown rubber with TRR added, the Mooney scorch time t of the solid tire crown rubber filled with MOMN-RGTR is 10 The shorter the time, the earlier the solid tire crown rubber filled with MOMN-RGTR enters the hot vulcanization stage. This relatively small change will not only prevent the solid tire crown rubber from scorching, but also improve the vulcanization efficiency. This is because the solid tire crown rubber filled with MOMN-RGTR has a lower Mooney viscosity and good fluidity, which enables the solid tire crown rubber to quickly fill the mold and complete the vulcanization process; in addition, the process vulcanization time t of the solid tire crown rubber filled with MOMN-RGTR is 90 and theoretical vulcanization time t 100 Both are lower than those filled with TRR solid tire crown rubber, with the maximum reduction reaching 10.4% and 15.4%, indicating that filling MOMN-RGTR can significantly improve the vulcanization efficiency.
[0145] The basic performance of the solid tire crown rubbers prepared in Examples 6 to 11 and Comparative Examples 7 to 11 was tested respectively, and the test results are shown in Table 8.
[0146] Table 8 Hardness, density and resilience of solid tire crown rubber obtained from Example 6 to Example 11 and Comparative Example 7 to Comparative Example 11
[0147]
[0148] It can be concluded from Table 8 that the hardness (Shore A) of the solid tire crown rubber filled with 10 to 60 parts of MOMN-RGTR is equivalent to or slightly higher than that of the solid tire crown rubber filled with 10 parts of TRR, and both meet the solid tire crown rubber hardness requirements (70±2). However, when the filling amount of MOMN-RGTR exceeds 60 parts, the hardness of the solid tire crown rubber will be lower than that of the solid tire crown rubber filled with TRR, and no longer meet the hardness standard of the solid tire crown rubber. In terms of density, there is little difference between the solid tire crown rubber filled with TRR and the solid tire crown rubber filled with MOMN-RGTR, and both meet the density requirements of the solid tire crown rubber (1.21±0.01g / cm 3 ). As for the rebound resilience, the rebound resilience of the solid tire crown rubber filled with MOMN-RGTR is equal to or less than that of the solid tire crown rubber filled with TRR. With the increase of the filling amount of MOMN-RGTR, the rebound resilience of the solid tire crown rubber shows a downward trend. This reason is consistent with the factors in the vulcanization characteristics analysis, mainly due to the reduction of the cross-linking degree of the solid tire crown rubber. However, it is worth noting that when the filling amount of MOMN-RGTR is in the range of 10 to 60 parts, the impact on the rebound resilience is relatively small, and the rebound resilience can still be maintained above 34, which does not affect the normal use of the solid tire crown rubber.
[0149] The hardness, tensile properties and aging properties of the solid tire crown rubbers prepared in Examples 6 to 11 and Comparative Examples 7 to 11 were tested respectively. The test results are shown in Table 9.
[0150] Table 9 Tensile properties and thermal oxidation aging properties of solid tire crown rubber obtained from Examples 6 to 11 and Comparative Examples 7 to 11
[0151]
[0152]
[0153] According to Table 9, when the filling amount of MOMN-RGTR exceeds 60 parts, the hardness of the solid tire crown rubber will decrease, which is lower than the standard of Shao A70±2, and therefore no longer meets the use requirements of the solid tire crown rubber. This phenomenon of reduced hardness is attributed to the reduction of the crosslinking density of the solid tire crown rubber. At the same time, with the increase of the filling amount of MOMN-RGTR, the tensile strength of the solid tire crown rubber shows a downward trend. However, when the filling amount is less than 50 parts, the tensile strength can still be maintained above 16MPa, the elongation at break exceeds 400%, and the 300% tensile stress is greater than 8MPa. These indicators all meet the use performance requirements of the solid tire crown rubber. Compared with the solid tire crown rubber of TRR filled with the same number of parts, the solid tire crown rubber filled with MOMN-RGTR is slightly insufficient in mechanical properties. This is mainly because the solid tire crown rubber filled with MOMN-RGTR has a low sol content and a high gel content, which leads to a reduced degree of crosslinking involved in the reaction. Nevertheless, after undergoing an aging test at 100℃×72h, the MOMN-RGTR solid tire crown rubber filled with the same number of parts showed better aging resistance indicators than the TRR solid tire crown rubber filled with the same number of parts, which indicates that the MOMN-RGTR solid tire crown rubber has relatively better aging resistance.
[0154] observe Figure 4 It is concluded that the tear strength of the solid tire core rubber filled with MOMN-RGTR is greater than that of the solid tire core rubber filled with TRR, and the tear strength of the latter is 69N / mm. With the increase of the filling ratio of MOMN-RGTR in the solid tire core rubber, the tear strength of the solid tire core rubber first increases and then decreases. Specifically, when the filling ratio of MOMN-RGTR is less than 50 parts, the tear strength remains at a high level, reaching a maximum of 99N / mm. This is due to the small particle size and large specific surface area characteristics of MOMN-RGTR. When the filling ratio is less than 50 parts, MOMN-RGTR can be evenly dispersed in the solid tire core rubber, and its gel particles form an interpenetrating network structure with the raw rubber matrix. This structure enhances the interaction between carbon black and the raw rubber matrix and between micro-nano recycled rubber and rubber, reduces the defective structure inside the solid tire core rubber, and thus gives the solid tire core rubber a stronger ability to resist crack growth. However, as the amount of MOMN-RGTR filled in the solid tire core rubber increases, the rubber content of the solid tire core rubber decreases significantly, and the bond energy between the cross-linking bonds weakens, causing the network structure formed by the solid tire core rubber to become unstable. This increase in instability reduces the ability of the solid tire core rubber to resist crack growth, which is manifested as a decrease in tearing performance.
[0155] observe Figure 5It is concluded that the solid tire core rubber filled with MOMN-RGTR shows significant superiority in compression heat generation temperature compared with the solid tire core rubber filled with TRR, and its compression heat generation temperature is much lower than the latter, with a specific value of 47.3°C. With the increase of the number of MOMN-RGTR filled in the solid tire core rubber, the compression heat generation temperature of the solid tire core rubber shows a trend of first increasing, then decreasing, and then increasing. Specifically, when the number of filled portions is less than 60, the compression heat generation temperature remains at a low level, all below 30°C, especially when filled with 30 portions, the compression heat generation temperature is only 21.9°C. This is due to the uniform distribution of MOMN-RGTR in the solid tire core rubber and the low viscosity. This distribution characteristic reduces the internal friction between the raw rubber matrix and the filler, so that when the tire is subjected to periodic compression stress, the hysteresis loss of the solid tire core rubber due to viscoelasticity is reduced, which is manifested in that during the compression process, the temperature rise of the solid tire core rubber filled with MOMN-RGTR is less than that of the solid tire core rubber filled with TRR. However, when the filling amount of MOMN-RGTR is greater than 60 parts, as the filling amount increases, the heat dissipation capacity of the solid tire core rubber gradually weakens, causing the heat generated by compression to accumulate inside the solid tire core rubber, thereby gradually increasing the temperature rise.
[0156] observe Figure 6 It is concluded that when 10 parts of TRR are filled in the core rubber of a solid tire, its surface shows agglomeration. In contrast, when 10 to 60 parts of MOMN-RGTR are filled, the surface of the solid tire core rubber is smooth, no obvious agglomeration is observed or only slight agglomeration is observed, indicating that MOMN-RGTR is evenly dispersed in the solid tire core rubber. However, as the filling amount of MOMN-RGTR increases further, although its agglomeration phenomenon increases, the degree of agglomeration is still lower than the degree of agglomeration of the solid tire core rubber when TRR is filled. This is due to the smaller particle size of MOMN-RGTR, which enables it to be dispersed more evenly in the solid tire core rubber. However, when the amount of MOMN-RGTR exceeds 60 parts, the difficulty of dispersion increases due to the large specific gravity of the filler. Under the same mixing conditions, the macroscopic phenomenon presented is "rubber lumps", which makes the surface of the solid tire core rubber rough.
[0157] observe Figure 7It was found that the tear strength of the solid tire crown rubber filled with 10 to 80 parts of MOMN-RGTR was higher than that of the solid tire crown rubber filled with TRR (80.2N / mm). As the filling amount of MOMN-RGTR increased, the tear strength of the solid tire crown rubber showed a trend of first increasing and then decreasing. When the filling amount was less than 50 parts, the tear strength remained at a high level, reaching a maximum of 93.77N / mm. However, a continued increase in the filling amount would lead to a significant decrease in the rubber content of the solid tire crown rubber, a weakening of the cross-linking bond energy, and a decrease in the stability of the network structure, which would in turn reduce the tearing performance.
[0158] observe Figure 8 It is found that the Akron wear volume of solid tire crown rubber filled with 10 to 60 parts of MOMN-RGTR is smaller than that of solid tire crown rubber filled with TRR (0.358 cm 3 / 1.61Km). With the increase of MOMN-RGTR filling amount, the wear volume of Akron of solid tire crown rubber tends to increase. However, when the filling amount is less than 50 parts, the wear volume remains at 0.4cm 3 / Below 1.61Km, meeting the wear performance requirements of solid tire crown rubber.
[0159] observe Fig. 9 It was concluded that the surface agglomeration of the solid tire crown rubber filled with 10 parts of TRR was significant. In contrast, at the same filling amount, the agglomeration degree of the solid tire crown rubber filled with MOMN-RGTR was lighter. When the filling amount was 10 to 50 parts, MOMN-RGTR was dispersed more evenly in the solid tire crown rubber, the surface of the solid tire crown rubber was smooth, and there was less or no agglomeration. However, with the increase of the filling amount of MOMN-RGTR, the agglomeration phenomenon gradually intensified. This is attributed to the small particle size of MOMN-RGTR, which is evenly dispersed when the filling amount is small, but when the filling amount exceeds 50 parts, due to the excessive amount of filler, the difficulty of dispersion increases, resulting in "rubber lumps" under the same mixing conditions, and the surface becomes rough.
[0160] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiment, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art can make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiment and all changes and modifications that fall within the scope of the present invention.
Claims
1. Application of micro-nano recycled rubber in the preparation of solid tire crown rubber.
2. The use of the micro-nano reclaimed rubber according to claim 1 in preparing solid tire crown rubber, characterized in that: The solid tire crown rubber is made of the following raw materials in parts by weight: Malaysian standard rubber-20#, 88 parts to 92 parts; styrene-butadiene rubber SBR1502, 8 parts to 12 parts; carbon black S660, 18 parts to 22 parts; super carbon black N220, 38 parts to 42 parts; filler CS-B, 23 parts to 27 parts; light truck tire rubber powder, 13 parts to 17 parts; ZnO, 4 parts to 6 parts; stearic acid SA, 2.3 parts to 2.7 parts; Antioxidant 4010 and antioxidant RD, 2.3 to 2.7 parts; dispersant CS-101A, 1.8 to 2.2 parts, low heat generation aid B-206, 1.8 to 2.2 parts; tear-resistant resin 2066, 1.8 to 2.2 parts; sulfur, 1.4 to 1.8 parts; accelerator NS, 0.5 to 0.9 parts; anti-scorch agent CTP, 0.1 to 0.3 parts; micro-nano recycled rubber, 10 to 60 parts.
3. The use of the micro-nano reclaimed rubber according to claim 2 in the preparation of solid tire crown rubber, characterized in that: The solid tire crown rubber is prepared according to the following steps: Malaysia standard rubber-20#, styrene-butadiene rubber SBR1502, super carbon black N220, filler CS-B, light truck tire rubber powder, stearic acid SA, ZnO, antioxidant, low heat generation additive B-206, tear-resistant resin 2066, anti-scorch agent CTP and dispersant CS-101A are mixed in sequence and then mixed for the first time to obtain tire crown masterbatch; The tire crown masterbatch is mixed for the second time to obtain a tire crown mixed rubber; Adding micro-nano reclaimed rubber, accelerator NS and sulfur to the crown mixed rubber in sequence for vulcanization to obtain crown vulcanized rubber; The crown vulcanized rubber is mixed for the third time to obtain the solid tire crown rubber.
4. The use of the micro-nano reclaimed rubber according to claim 3 in preparing solid tire crown rubber, characterized in that: The temperatures for the first mixing, the second mixing, the third mixing and the vulcanization are all 100°C to 110°C.
5. Application of micro-nano recycled rubber in the preparation of solid tire core rubber.
6. The use of the micro-nano reclaimed rubber in the preparation of solid tire core rubber according to claim 5, characterized in that: The solid tire core rubber is made of the following raw materials in parts by weight: Malaysian standard rubber-20#, 78 to 82 parts; butadiene rubber BR9000, 18 to 22 parts; low structure medium reinforcement carbon black N550, 28.8 to 31.2 parts; high wear resistant carbon black N330, 19.2 to 20.8 parts; white carbon black, 4.5 to 5.5 parts; silicone coupling agent Si-69, 0.4 to 0.6 parts; ZnO, 4.5 to 5.5 parts; hard Fatty acid SA, 2.5 to 3.5 parts; coumarone 1.5 to 2.5 parts; antioxidant RD and antioxidant BLE, 3.0 to 4.0 parts; dispersant, 1.8 to 2.2 parts, low heat generating aid, 1.8 to 2.2 parts; sulfur, 1.4 to 1.8 parts; accelerator NS, accelerator DM, accelerator DTDM, 1.4 to 1.8 parts; micro-nano recycled rubber, 10 to 50 parts.
7. The use of the micro-nano reclaimed rubber in the preparation of solid tire core rubber according to claim 6, characterized in that: The solid tire core rubber is prepared according to the following steps: Malaysian standard rubber-20#, BR9000, low-structure medium-reinforced carbon black N550, medium-super carbon black N220, white carbon black, silicone coupling agent Si-69, stearic acid SA, ZnO, coumarone, antioxidant RD and antioxidant BLE, low heat generation additive and dispersant are mixed in sequence and then mixed for the first time to obtain a tire core masterbatch; The core rubber masterbatch is mixed for the second time to obtain a core rubber mix; Adding micro-nano reclaimed rubber, accelerator NS, accelerator DM, accelerator DTDM and sulfur to the tire core mixed rubber in sequence for vulcanization to obtain tire core vulcanized rubber; The core vulcanized rubber is mixed for the third time to obtain a solid tire core rubber.
8. The use of the micro-nano reclaimed rubber in the preparation of solid tire core rubber according to claim 7, characterized in that: The temperatures for the first mixing, the second mixing, the third mixing and the vulcanization are all 100°C to 110°C.
9. The use of the micro-nano reclaimed rubber in the preparation of solid tire crown rubber according to claim 2 or the use of the micro-nano reclaimed rubber in the preparation of solid tire core rubber according to claim 6, characterized in that: The Mooney viscosity of the micro-nano regenerated rubber is 40.8-42.5, the sol content is 41.7%-45%, and the gel content is 19%-22.3%.
10. The use of the micro-nano reclaimed rubber in the preparation of solid tire crown rubber according to claim 2 or the use of the micro-nano reclaimed rubber in the preparation of solid tire core rubber according to claim 6, characterized in that: Micro-nano regenerated rubber is prepared according to the following steps: The truck tire rubber powder was placed in a tank-type thermal oxidation degradation device, pulsed air was introduced, and thermal oxidation degradation was carried out at 190℃~202℃ for 10 minutes to obtain micro-nano regenerated rubber.